2014
DOI: 10.7314/apjcp.2014.15.14.5889
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between EGFR Over-expression and Clinicopathologic Characteristics in Squamous Cell Carcinoma of the Esophagus: A Meta-analysis

Abstract: Over-expression of epidermal growth factor receptor (EGFR) has been identified as a common feature associated with clinical outcome in many types of cancer, including squamous cell carcinoma of the oesophagus (SCCO). However, the clinical importance of EGFR over-expression in SCCO remains unsettled as conflicting results exist. Therefore we carried out the present meta-analysis of published studies for clarification. A total of 13 studies including 1, 150 patients were enrolled. EGFR over-expression was positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
0
14
1
Order By: Relevance
“…About 50% of patients were found with the advanced period of esophageal cancer when diagnosed, with unfavorable prognosis, about 6~8 months of natural course, 5%~7% five-year survival rate (; Liu et al, 2014;Mai et al, 2014;Zhao et al, 2014;Jiang et al, 2014;Wang et al, 2014;Stefani et al, 2014). Additionally, even though patients accepted surgical treatment, there still exists postoperative recurrence and metastasis in nearly 90% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…About 50% of patients were found with the advanced period of esophageal cancer when diagnosed, with unfavorable prognosis, about 6~8 months of natural course, 5%~7% five-year survival rate (; Liu et al, 2014;Mai et al, 2014;Zhao et al, 2014;Jiang et al, 2014;Wang et al, 2014;Stefani et al, 2014). Additionally, even though patients accepted surgical treatment, there still exists postoperative recurrence and metastasis in nearly 90% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulation of the EGFR signaling pathway through overexpression or hyperactivation is associated with tumor development (23,25,26). A meta-analysis demonstrated that the rate of EGFR overexpression in ESCC is high and EGFR expression levels are a potential predictor of the T stage (tumor-node-metastasis classification system) (27), vascular invasion and overall survival (27). By contrast, Aichler et al (28) reported that EGFR is an independent adverse prognostic factor in esophageal adenocarcinoma patients treated with cisplatin-based neoadjuvant chemotherapy; therefore, targeting EGFR may be a novel therapeutic approach in the management of ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…About 50% of patients with EC were found with advanced disease at diagnosis, with unfavorable prognosis, and 5%~7% five-year survival rate (Jiang et al, 2014;Wang et al, 2014). Additionally, even though patients accepted surgical treatment, there still exists postoperative recurrence and metastasis in nearly 90% of patients.…”
Section: Discussionmentioning
confidence: 99%